Effect of Thermal Treatment on Selected Fire Safety Features of Tropical Wood - Linda Makovicka Osvaldova; Miroslav Gasparik; Javier Ramon Sotomayor Castellanos; Frank Markert; Patricia Kadlicova; Hana Cekovska (Communications - Scientific letters of the University of Zilina, 2018)
The subject matter of the article is thermally modified tropical wood (Meranti and Merbau) and its reaction on fire. Thermal treatment of wood (thermal wood) is a new technology of wood treatment improving its physical and biological properties and increasing its resistance to biological wood destroying processes and atmospheric effects. The fire and technical properties of thermal wood, especially its reaction to fire, have not been studied sufficiently. The latter is the subject matter of this article. A comparison is made to describe the influence of process temperatures of the thermal modification of selected tropical woody plants. Experimental equipment was non-standardized laboratory equipment using a flame source of higher intensity (flame burner - propane-butane) affecting the test sample in an open environment. This is a simulation of an actual fire. The performance of the thermally treated wood (20 °C, 160 °C, 180 °C) is evaluated by measuring the weight loss and the burning rate. The results are presented in tables and diagrams and are statistically evaluated. This study investigated the effects of the thermal treatment of Merbau and Meranti wood on selected burning characteristics. The results obtained from raw (untreated) wood test specimens were compared to results obtained from the test specimens subjected to thermal treatment at 160 °C, 180 °C and 210 °C. The monitored characteristics were weight loss and the burn rate. The results showed that the thermal treatment of Merbau and Meranti wood significantly increased its flammability and accelerated its combustion. In addition, its burn rate was higher than in untreated wood, reflecting that it is necessary to add fire retardants to thermally treated Merbau and Meranti wood.